Evaluasi Kinerja Pegawai Negeri Sipil Dalam Meningkatkan Pelayanan Publik Di Kantor Camat Tompaso Kabupaten Minahasa - Lumentah, Jeferson Glandy; Posumah, Jhonny Hanny; Ogotan, Martha (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Sub-district as a public service agency has a duty to provide services to the public, sothat the Civil Service will also determine the success of the public service. This research is toanswer how the performance of the Civil Service to Improve Public Services Head officeTompaso Minahasa,This study uses a qualitative method. In this case the performanceindicators used are productivity, kaualitas service, responsiveness, renponsibilitas, andaccountability. Informants in this study were taken from the community, the old law, and anemployee at the office of Head Tompaso (7 people), Law Tua (4 people), and people (5 people) ofdata collection by interview: while the analysis of data using analysis techniques interactivemodel of Miles and Huberman. The results showed: (1) The level of productivity is quite goodviews from the successful implementation of programs and activities that have been set. (2)Quality of service is pretty good views of the coordination of the Civil Service in providingservices easy, fast, transparancy, and means. (3) The level of responsiveness is quite good, inresponse to all the needs and complaints of the public. (4) Level of Responsibility quite well,judging from the utilization of human resources potential of the Civil Service. (5) Level ofAccountability pretty good views of the accountability system is done either to local governmentsand to the public. Based on the results of these studies conclude that the Civil ServicePerformance Evaluation In Improving Public Services Head office Tompaso Minahasa prettygood views of the productivity aspect, Quality service, Responsiveness, Responsibility, andAccountability.Keywords: Performance Evaluation of Civil Servants.